(untitled) (Anwer Khan Modern Medical College Journal, 2020)
Background: Eclampsia is defined as the development of seizures that cannot be attributed to other causes and /or unexplained coma during pregnancy or puerperium in a woman with pre-eclampsia. The purpose of this hospital based observational study is to evaluate the extent of the problem and to estimate the associate of foetal and maternal complications Methodology: The observational study was carried out Department of Obstetrics and Gynaecology in 250 bedded general Hospital Tangail from January 2015 to November 2017. All on the diagnosed patients of eclampsia were included in this study. Results: Regarding types of eclampsia 187(62.3%) patients had antepartum eclampsia, 78(26.0%) had postpartum eclampsia and 35(11.7%) had intrapartum eclampsia. Majority (57.0%) patients had 5-9 times of convulsion, 65(21.7%) had >10 times and 64(21.3%) had <5 times of convulsion. Most (95.0%) patients had cesarean section and 15(5.0%) had normal vaginal delivery (NVD). Maternal alive was found 293(97.7%) and death was 7(2.3%). Male baby was found 203(67.7%) and female baby was 97(32.3%). More than three fourth (75.7%) babies had weight 2.5-4.0 kg. Alive babies were found 282(94.0%), neonatal death was 8(2.7%) and intrauterine death was 10(3.3%). Conclusion: Improving ante-natal and emergency obstetric and neonatal care is mandatory to improve the outcome. Anwer Khan Modern Medical College Journal Vol. 11, No. 1: Jan 2020, P 11-15